Relatividade geral com acoplamentos dependentes de escala e dimensões extras: consequências astrofísicas e cosmológicas - Bertini, Nicolas Ribeiro (2022)
General relativity extensions seek to resolve observational conflicts or implement new principles keeping the general relativity as a limiting case. Here we consider two classes of extended gravitaty: one in which the constants of general relativity G and